Forge : seeds of America - Anderson, Laurie Halse (New York : Atheneum Books for Young Readers, 2010)
Separated from his friend Isabel after their daring escape from slavery, fifteen-year-old Curzon serves as a free man in the Continental Army at Valley Forge until he and Isabel are thrown together again, as slaves once more.
Sequel to: Chains.
Keywords: Pennsylvania -- History -- Revolution, 1775-1783 -- Juvenile fiction; Valley Forge (Pa.) -- History -- 18th century -- Juvenile fiction; Soldiers -- Juvenile fiction; African Americans -- Juvenile fiction; Freed persons -- Juvenile fiction; Slavery -- Juvenile fiction; Pennsylvania -- History -- Revolution, 1775-1783 -- Fiction; Valley Forge (Pa.) -- History -- 18th century -- Fiction; Soldiers -- Fiction; African Americans -- Fiction; Freed persons -- Fiction; Slavery -- Fiction; United States -- History -- Revolution, 1775-1783 -- Fiction